Lacrimal caruncle nevus associated with Rubinstein–Taybi syndrome - Pogrzebielski, Arkadiusz; Piwowarczyk, Anna; Kobylarz, Joanna; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
We present a 28-year old man with diagnosed Rubinstein–Taybi syndrome (RSTS), known as „Broad thumb – Hallux syndrome” with co-existing lacrimal caruncle tumor. Because of the documented enlargement of the lacrimal caruncle mass and known increased risk to develop malignancies in RSTS patients we decided to perform excisional biopsy, which revealed caruncle nevus. To our knowledge this is the first description of such an association.